The US-China trade war and the emergence of market power in commodity markets. Issue 43 (14th September 2022) - Fedoseeva, Svetlana; Zeidan, Rodrigo
ABSTRACT: The article explores the indirect link between the trade war between China-US and deforestation in Brazil. China imposed tariffs that have eliminated American soy exports by November 2018. Higher soybean prices usually increase deforestation in Brazil. We estimate nonlinear autoregressive distributed lag models combined with multiple breakpoint tests to analyze price transmission changes over time. We show that market power emerges in the short run, while long-run price pass-through is close to complete. Extra profits from unexpected market power should induce land clearing for expanding soy production, a problem compounded by lax regulation, and reduced budgets for combating deforestation in Brazil. Results also suggest that effects on deforestation rates should be temporary. Given that the covid19 pandemic brings about a similar shock to global food markers, particularly demand for Brazilian soy, we expect a similar pattern of emergence of market power in the short but not long-run.